Development and characterization of chitosan-PEG-TAT nanoparticles for the intracellular delivery of siRNA - Malhotra M (Dove Medical Press, 2013)
Meenakshi Malhotra,1 Catherine Tomaro-Duchesneau,1 Shyamali Saha,2 Imen Kahouli,3 Satya Prakash11Biomedical Technology and Cell Therapy Research Laboratory, Department of Biomedical Engineering, Faculty of Medicine, 2Faculty of Dentistry, 3Department of Experimental Medicine, McGill University, Montreal, QC, CanadaAbstract: Recently, cell-penetrating peptides have been proposed to translocate antibodies, proteins, and other molecules in targeted drug delivery. The proposed study presents the synthesis and characterization of a peptide-based chitosan nanoparticle for small interfering RNA (siRNA) delivery, in-vitro. Specifically, the synthesis included polyethylene glycol (PEG), a hydrophilic polymer, and trans-activated transcription (TAT) peptide, which were chemically conjugated on the chitosan polymer. The conjugation was achieved using N-Hydroxysuccinimide-PEG-maleimide (heterobifunctional PEG) as a cross-linker, with the bifunctional PEG facilitating the amidation reaction through its N-Hydroxysuccinimide group and reacting with the amines on chitosan. At the other end of PEG, the maleimide group was chemically conjugated with the cysteine-modified TAT peptide. The degree of substitution on chitosan with PEG and on PEG with TAT was confirmed using colorimetric assays. The resultant polymer was used to form nanoparticles complexing siRNA, which were then characterized for particle size, morphology, cellular uptake, and cytotoxicity. The nanoparticles were tested in-vitro on mouse neuroblastoma cells (Neuro2a). Particle size and surface charge were characterized and an optimal pH condition and PEG molecular weight were determined to form sterically stable nanoparticles. Results indicate 7.5% of the amines in chitosan polymer were conjugated to the PEG and complete conjugation of TAT peptide was observed on the synthesized PEGylated chitosan polymer. Compared with unmodified chitosan nanoparticles, the nanoparticles formed at pH 6 were monodispersed and of <100 nm in size, exhibiting maximum cell transfection ability and very low cytotoxicity. Thus, this research may be of significance in translocating biotherapeutic molecules for intracellular delivery applications.Keywords: chemical conjugation, peptide, transfection, polymer, synthesis, in-vitro